2021
DOI: 10.1142/s0129065721500167
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Center Validation Study of Automated Classification of Pathological Slowing in Adult Scalp Electroencephalograms Via Frequency Features

Abstract: Pathological slowing in the electroencephalogram (EEG) is widely investigated for the diagnosis of neurological disorders. Currently, the gold standard for slowing detection is the visual inspection of the EEG by experts, which is time-consuming and subjective. To address those issues, we propose three automated approaches to detect slowing in EEG: Threshold-based Detection System (TDS), Shallow Learning-based Detection System (SLDS), and Deep Learning-based Detection System (DLDS). These systems are evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…We also achieved LOIO BAC of 76.1% and LOSO BAC of 69.3% with an ensemble of three components: ConvNet for detecting IEDs, Template Matching for detecting IEDs, and Spectral features for classifying EEGs. 10 In another multi-center study, Peh et al 25 proposed an EEG classifier based on slowing and reported an LOIO BAC 82.0% and LOSO BAC of 81.8%. Marleen et al 31 achieved an AUC of 0.94 with 2D ConvNet for IED detection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also achieved LOIO BAC of 76.1% and LOSO BAC of 69.3% with an ensemble of three components: ConvNet for detecting IEDs, Template Matching for detecting IEDs, and Spectral features for classifying EEGs. 10 In another multi-center study, Peh et al 25 proposed an EEG classifier based on slowing and reported an LOIO BAC 82.0% and LOSO BAC of 81.8%. Marleen et al 31 achieved an AUC of 0.94 with 2D ConvNet for IED detection.…”
Section: Introductionmentioning
confidence: 99%
“…Marleen et al 31 achieved an AUC of 0.94 with 2D ConvNet for IED detection. In these five studies, 6,8,10,25,30 the ConvNet detector is investigated with only the preprocessed EEG signal. In our preliminary study, we proposed a 1D ConvNet that exploited frequency sub-bands as features for the detection of IEDs, and we tested it on a dataset containing 554 EEGs.…”
Section: Introductionmentioning
confidence: 99%
“…We perform seizure detection őrst at individual channels (channel-level detection), next at multi-channel segments (segment-level detection), and at last, we detect the start and end points of the seizures in the entire multi-channel EEG (EEG-level detection) [65][66][67] (see Supplementary Figure 1). The pipeline of the proposed seizure detector is displayed in Figure 3.…”
Section: Seizure Detector Pipelinementioning
confidence: 99%
“…We assess the channel-and segment-level seizure classiőers through the following metrics: accuracy (ACC), balanced accuracy (BAC), sensitivity (SEN), speciőcity (SPE), F1 score (F1), and expected calibration error (ECE) 70 . As the seizure and non-seizure classes are imbalanced, we evaluate the results mainly in terms of BAC 67 .…”
Section: Channel-and Segment-level Evaluation Metricmentioning
confidence: 99%
See 1 more Smart Citation